The Microstructure and the Phase Stability of a Cu–30at.%Al Alloy Obtained by Reactive Milling and Quenching - Giordana, María Florencia (2020)
The phase stability of a Cu–30at.%Al milled and quenched is studied by differential scanning calorimetry and in situ high-temperature X-ray diffraction (HT-XRD). This analysis was performed from room temperature to 700 °C. The grain growth at fixed temperatures was analyzed by HT-XRD. The size of the γ2 phase grains do not change at a constant temperature with the time at temperatures below 600 °C. This behavior was attributed to the pulling force resulting from the presence of nanometric grains. The presence of nanometric grains was confirmed by TEM. The lack of grain size growth at a constant temperature is a promising result for the technological application of the Cu–30at.%Al milled and quenched as a shape memory alloy.